The Form And Style Of Presentation Of The Remo Putri Dance Ludruk Karya Budaya Mojokerto: Form And Style Of Presentation Of The Remo Putri Dance Ludruk Karya Budaya Mojokerto - Kusumawati, Heni; ., Trisakti (Solah, 2025)
Remo Putri Dance is the opening dance in the Ludruk Karya Budaya Mojokerto performance danced by several Travesty Ludruk Karya Budaya Mojokerto artists. The Form and Presentation Style of Remo Putri Dance has characteristics that are unique to Ludruk Karya Budaya Mojokerto. The purpose of this study is to describe the Presentation Form of Remo Putri Dance and the Presentation Style of Remo Putri Dance in Ludruk Karya Budaya Mojokerto. To answer the research objectives and to obtain relevant data, the author uses a research approach through a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The results of the study on the Presentation Form include movements, floor patterns, make-up, and costumes of the Remo Putri Ludruk Karya Budaya Dance. The Remo Putri Ludruk Karya Budaya Mojokerto Dance has simple movements that highlight graceful and feminine characters. The choreography reflects a series of movements developed through collaborative practices between veteran dancers in 2018 and new dancers in 2024. Floor patterns, make-up, costumes, and accessories are also closely monitored to support the dancers' performances, especially for Travesty Ludruk Karya Budaya artists. The results of the research on Presentation Style include the emblematic style that emphasizes expressive movements, which plays a crucial role in depicting female characters, exemplifying the flexibility of local culture, and combining a harmonious blend of dance and character representation.